Pendekatan Psikologis dalam Mengatasi Gangguan Berpikir pada Anak Sekolah Dasar - Isna Sitti Alfina; Ibnu Muthi (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
This study aims to examine the effectiveness of psychological approaches in overcoming thinking disorders in elementary school children. The background of this study is the increasing cases of thinking disorders such as difficulty distinguishing reality, irrational thinking, and rigid thought patterns, which have a negative impact on children's learning processes and social interactions. Unfortunately, these disorders are often not identified early due to a lack of understanding from teachers and parents of the psychological symptoms that appear. This study uses a qualitative approach with a literature review method (library research). Data sources come from accredited journals, child development psychology books, and relevant previous research results. The data analysis technique uses the Miles and Huberman model which includes the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that psychological approaches such as cognitive-behavioral therapy (CBT), individual counseling, and play therapy have proven effective in helping children recognize, manage, and regulate negative thought patterns. This approach also improves children's communication skills and self-confidence. The success of the intervention is greatly influenced by the involvement of teachers and parents, as well as a safe and supportive learning environment. However, limited resources and a lack of professional staff are major obstacles in implementing interventions in elementary schools.